Heavy Metals Content in the Water Lakes of Barlinek-Gorzów Landscape Park (North-West Poland) - Daniszewski, Piotr; Konieczny, Ryszard (Asian Journal of Chemistry, 2014)
The present research work deals with the quantification of toxic heavy metals in the water samples collected from different lakes viz., Barlineckie lake, Glebokie lake, Lubiszewko lake and Przyleg lake of the Barlinek-Gorzów Landscape Park (North-West Poland). For this we took samples from Barlineckie lake, Glebokie lake, Lubiszewko lake and Przyleg lake for analysis of various heavy metals such as cadmium, chromium, copper, mercury, lead, zinc and nickel.